2005
DOI: 10.1606/1044-3894.1878
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Behavioral Health Services within a Primary Care Center in a Rural Setting

Abstract: The Rural Care Program is a pilot program that has been developed to integrate generalist social work practice into a primary care center. The premise of the program is to provide a holistic model of health care, with licensed masters-level social workers providing behavioral health therapeutic interventions in addition to case management, community development, and information and referral. This article describes the development and implementation process of the program, emphasizing the effectiveness of rural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Clinical social workers, as allied health professionals, are well established in the US healthcare system, often providing specialist mental health interventions as part of multidisciplinary teams (Bauer et al . , Sommers et al . , Wetta‐Hall et al .…”
Section: Introductionmentioning
confidence: 97%
“…Clinical social workers, as allied health professionals, are well established in the US healthcare system, often providing specialist mental health interventions as part of multidisciplinary teams (Bauer et al . , Sommers et al . , Wetta‐Hall et al .…”
Section: Introductionmentioning
confidence: 97%
“…In addition, characteristics of collaborative processes were measured, for example, the number of referrals,37 39 43 44 team climate, team development32 45–47 and professionals’ job satisfaction 31–33 46 48 49. Cost-effectiveness measurements were addressed in three studies 30 45 50…”
Section: Resultsmentioning
confidence: 99%
“…Interventions can include a host of different services such as linking individuals and families with available community resources and supports, providing therapeutic services, supportive counseling and grief counseling, completing discharge planning, helping an individual to expand and strengthen their network of social supports, or engaging in crisis intervention (Bauer et al, 2005;14 Canadian Association of Social Work, 2003;Davis et al, 2004;Marino, Weinman, & Soudelier, 2001). Interventions represent another role of social workers working in primary health care settings.…”
Section: Competencies and The Role Of Social Work In Primary Health Carementioning
confidence: 99%
“…Appropriate referrals represent an important contribution to individual and family health and 15 social well being (Sands, 2000 as cited in Bentley, Walsh, & Farmer, 2005) and it has been suggested that prompt and timely referrals may even be connected to the prevention of unnecessary suffering for many clients (Ross & Hardy, 1999 as cited in Bentley, Walsh, & Farmer, 2005). Community resources such as support groups, education programs, and social support services can work to further improve the health and social well being of individuals and families and work to curtail further involvement in the health care system (Bauer et al, 2005;Berkman et al, 2005).…”
Section: Competencies and The Role Of Social Work In Primary Health Carementioning
confidence: 99%
See 1 more Smart Citation